The Roles of Leadership, Regional Government, DPRD, and Local Revenue on Business Licensing’s Effectiveness - Thesia, John Kennedy; Hubeis, Musa; Adiwisastra, Josy; Supriyatno, Budi (International Journal Labs, 2022)
Every implementation of autonomy affairs is expected to achieve effective and efficient use of resources. His desire to create an image that local governments can use resources, both in the form of human resources, regional revenue budgets, equipment and work procedures in carrying out their main duties effectively and efficiently in good governance. This study aims to analyze the influence of leadership, the role of local government, the role of the Jayapura City DPRD and local revenues together to partially compile the effectiveness of business license in Jayapura City. To obtain a comprehensive and in-depth picture, a descriptive method with a quantitative approach is used to analyze existing empirical data and correlate with concepts related to special autonomy policies. First, leadership has a partial significant effect on the effectiveness of business licensing in Jayapura City. Second, the role of local governments partially has a significant effect on the effectiveness of business license in Jayapura City. Third, the role of the DPRD partially has a significant effect on the effectiveness of nusaha license in Jayapura City. Fourth, the original regional income partially affects the effectiveness of business licensing in Jayapura City. Fifth, leadership, the role of local governments, the role of the DPRD and local revenue simultaneously have a significant effect on the effectiveness of business license in Jayapura City.